2020
DOI: 10.34239/ajops.v3n1.201
|View full text |Cite
|
Sign up to set email alerts
|

How can AHPRA improve compliance of health practitioner advertising?

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…20 Furthermore, a lack of action (perceived or otherwise) by AHPRA in the face of clear breaches by others, may discourage registrants from modifying their own advertising practices. 21 Further research is required to investigate why contravention of regulatory guidance regarding advertising guidance is so commonplace. A 2019 study found that over 80% of the websites of plastic surgeons in Australia were found to be compliant with the AHPRA advertising guidance, so greater compliance among the dental profession should be possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Furthermore, a lack of action (perceived or otherwise) by AHPRA in the face of clear breaches by others, may discourage registrants from modifying their own advertising practices. 21 Further research is required to investigate why contravention of regulatory guidance regarding advertising guidance is so commonplace. A 2019 study found that over 80% of the websites of plastic surgeons in Australia were found to be compliant with the AHPRA advertising guidance, so greater compliance among the dental profession should be possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the flexibility and agility associated with this regulatory model can result in uncertainty and (perceived) inconsistency over what is acceptable to advertise 20 . Furthermore, a lack of action (perceived or otherwise) by AHPRA in the face of clear breaches by others, may discourage registrants from modifying their own advertising practices 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation